Evaluation of the prerequisite programs for the Hazard Analysis and Critical Control Points Systemin some food factories in the Asir region, Saudi Arabia - Abumalih, Adel Mohammed (Journal of agricultural, environmental and veterinary sciences, 2023)
The objective of conducting the study is to evaluate the effective application of the HACCP system in some food factories in the Asir region in the Kingdom of Saudi Arabia and to study the possible ways to urge the food establishment to implement the HACCP system to ensure the safety of food products, also the extent of commitment of the food factories will be evaluated Effective application of the HACCP system requirements. Samples of the final products were drawn from the factories under study and referred for laboratory examination to evaluate the final outputs of good manufacturing practices and the effective application of the HACCP system. The study was conducted on a sample of 50 factories from the factories of the Asir region, which were selected randomly, in order to assess the status of the factories and to know the extent of the commitment of the factories of the Asir region to apply the foundations of good manufacturing and storage and the extent of commitment to the technical regulations circulated by the Food and Drug Authority and the standard technical specifications. As it became clear from the results of the study that most of the food factories under study in the Asir region were good in applying the technical requirements, in particular the factories located within the newly established industrial cities, where the percentage of applying the technical requirements in the final product storage warehouses was good by (87%), and the production department Excellent rate (90%), and the treatment area was good (71%). The researcher presented recommendations and possible and appropriate solutions, including, but not limited to, training workers and educating them about the importance of adhering to good health practices and obligating food manufacturers to apply the Hazard Analysis and Critical Control Points (HACCP) system to ensure the safety of the manufactured food product and the consumer’s access to healthy, safe and high quality food that is free of pathogens.